WORSILEAR (Word Square Interactive Learning): Media Pembelajaran Akuntansi Berbasis Aplikasi Sebagai Upaya Peningkatan Pemahaman Akuntansi Dasar Siswa Sekolah Menengah Kejuruan - Intan Asih Moelyani; Farida Amelia; Fath Thoriqi Haqi S; Primasa Minerva Nagari (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
The challenge in realizing quality education requires educators to be more creative, innovative, and inspiring in designing learning activities. This is carried out as well as preparation to welcome Indonesia's golden generation in 2045. In addition, in the accounting world, the role of educator accountants is very important to form reliable millennial accountants with high competitiveness. This research is a media development research that raises the incorporation of interactive media using the word square learning model with the aim of facilitating the understanding of accounting material for students so that it can motivate students to be enthusiastic about learning and obtain maximum learning outcomes. Learning activities through interactive media are learning using technology-based tools. Meanwhile, the model in word square learning is a learning model with the same level of similarity as the crossword puzzle learning model. In word square learning, answers are available but they are disguised using the addition of letters or numbers, as well as the addition of boxes as a distraction with the aim of training students' critical and conscientious attitude. The method in this study, namely the research and development method of the ADDIE model. Based on the research results that have been obtained, it can be concluded that the learning process is more interesting if it uses a combination of technology-based interactive media with the word square model. This research reaches the design stage of the application to be developed. This research can be improved later with practical trials in the field on students in the classroom.